Metabolic syndrome is associated with and predicted by resting heart rate: a cross-sectional and longitudinal study - Jiang, Xiongjing; Liu, Xiaoxue; Wu, Shouling; Zhang, Gus Q; Peng, Meng; Wu, Yuntao; Zheng, Xiaoming; Ruan, Chunyu; Zhang, Weiguo (Heart (British Cardiac Society), 2015)
Objective Although higher resting heart rate (RHR) has emerged as a predictor for lifespan, the underlying mechanisms remain obscure. The present study investigates whether a positive relationship exists between RHR and metabolic syndrome (MetS) and whether RHR predicts future MetS. Methods A cohort of 89 860 participants were surveyed during 2006–2007 in Kailuan/Tangshan, China. MetS was diagnosed when a participant presented at least three of the following: abdominal adiposity, low high density lipoprotein-cholesterol, high triglycerides, hypertension or impaired fasting glucose. RHR was derived from ECG recordings and subjects were stratified based on RHR. Some participants without MetS at baseline were followed-up for 4 years. Results At baseline, 23 150 participants (25.76%) had MetS. There was a positive association between RHR and MetS. The OR of having MetS was 1.49 (95% CI 1.32 to 1.69) in subjects with RHR at 95–104 compared with those at 55–64 beats per minute (bpm) (reference), after adjusting for variables including age, sex, education, cigarette smoking, alcohol drinking, physical activities, body mass index, hypertension, diabetes, hyperlipidaemia, inflammatory biomarkers and renal function. More importantly, when 43 725 individuals from the original study without MetS at baseline were followed-up, higher RHR was found to predict greater risk of MetS incidence. The OR of developing MetS 4 years later was 1.41 (95% CI 1.21 to 1.65) in subjects with RHR at 95–104 bpm compared with reference, after all adjustments. Conclusions Our cross-sectional and longitudinal findings provide evidence that RHR is an independent risk factor for existing MetS and a powerful predictor for future incidence of MetS.